IMPROVING TEACHERS' WORK PRODUCTIVITY THROUGH THE DEVELOPMENT OF A GROWTH MINDSET, TRANSFORMATIONAL LEADERSHIP, COLLABORATION, WORK MOTIVATION, AND CREATIVITY - Fitria Iswari; Sri Setyaningsih; Suhendra Suhendra (Yayasan Education and Social Center, 2026)
This study aims to test the hypothesis that independent variables namely, growth mindset, transformational leadership, and cooperation along with intervening variables namely, work motivation and creativity influence the dependent variable of teacher work productivity. The research employed a quantitative method and tested 13 research hypotheses. The respondents were 140 public special education school (SLB) teachers in the Province of Jakarta. The instruments used for each research variable were questionnaires that had previously undergone validity and reliability testing. Data analysis employed path analysis using the SEM-PLS 3 software. The results indicated that 6 hypotheses were accepted regarding direct effects, while 3 hypotheses were rejected. In testing indirect effects, 2 hypotheses were accepted, and 2 were rejected. Furthermore, using SITOREM analysis to classify indicators within the research variables, 18 indicators were improved, and 13 were retained or developed. It is hoped that the implications of this study can improve the work productivity of public special education teachers in Jakarta Province by strengthening a growth mindset, transformational leadership, cooperation, work motivation, and creativity.